"I'll be okay": survivors' perspectives on participation in domestic violence research - Dragiewicz, Molly (Journal of family violence, 2023)
Purpose: This article investigates survivors’ experiences participating in research interviews about technology-facilitated domestic violence. University research ethics committees often assume that participating in research on violence and abuse is distressing for survivors. Scholars have called for research testing this assumption. This article contributes to the evidence base on the benefits and risks of asking research participants about gender-based violence. Methods: This article is based on semi-structured interviews with 20 Australian domestic violence survivors. Template analysis was used to code the interviews and develop key themes. Results: The five themes derived from the interviews include reflection on recovery and personal growth; helping other women; rejecting victim-shaming; empowerment; and the importance of timing. Conclusion: All participants reported positive experiences taking part in the study. However, the authors noticed substantial differences in participant narratives across service cohorts. The implications of recruiting through channels associated with different points in trauma trajectories warrant attention.